THE PERSONALITY OF THE DIRECTOR OF THE SCHOOL AS A SUBJECT OF SCIENTIFIC DISCOURSE (60-80's XX CENTURY) - Zadorozhna-Knyagnitska, Leninа V. (Educological discourse, 2014)
In the article the views of the scientists on the identity of the head of the educational institution, the nature and components of managerial skills in the period of «developed socialism» (60-80-ies Twentieth century) are considered; normative documents that reveal the requirements for the Director of the school and the content of his leadership are analyzed; «Lenin’s style of management» as the basis of management skills of the head of the institution is described; the results of the analysis of pedagogical works by Russian scientists on the issues of school management are outlined.